Ez Hanger / Muhammad Faizal A Razak ... [et al.] - A Razak, Muhammad Faizal; Mahar Affandi, Din Iqbal; Mohd Kamil, Kamarul Bahrin; Engku Husin, Engku Muhammad Azlan; Roma Isia, Isfarizal (2005)
KJP 365 is a compulsory course that we must finish to get a diploma. We as a group combined our ideas and creativity to achieve our goal to finish our design according to the time given by our faculty. From that on we have create a product that called EZ HANGER. Our project is easy to operate and suitable for all houses and designed according to the problems that always occur when we says about hungering a cloth at area that have a of lack space